Media Rituals in Eusébio's Exequies - Mateus,Samuel (2016)
While celebrating collective representation, the media can be seen as spaces of ritualization that are fundamental to the consolidation of wider social values. In this paper we give an empirical frame to the concept of “media rituals” considering it as an entrenched symbolic practice that could be traceable in Eusébio's exequies television broadcasting. Three sorts of media rituals are identified: rituals dealing with immediacy, rituals dealing with collective prominence and rituals dealing with the revelation of reality. Each media ritual exemplifies how a space of comprehensive ritualization is erected. It is through this generalized and mediated ritualization that the idea of a major social occurrence is refreshed and worked through.